2020
DOI: 10.1021/acs.langmuir.0c00079
|View full text |Cite
|
Sign up to set email alerts
|

Greater SERS Activity of Ligand-Stabilized Gold Nanostars with Sharp Branches

Abstract: Sharp branches of gold nanostars are critical in tuning the plasmonic properties of these nanostars and maximizing the activities in surface-enhanced Raman scattering (SERS). The interaction between the capping ligands and nanostars plays an essential role in determining the morphology of the branches on the gold nanostars. In this Article, we show that 4-mercapto benzoic acid can effectively control the morphology of branched gold nanostars, and these gold nanostars can be used for the colloidal SERS detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 63 publications
(91 reference statements)
1
37
0
Order By: Relevance
“…Gold nanostars (AuNSs) are of special interest because morphological modifications, such as number of tips and their length, can be used to tune the position of the band of localized surface plasmon resonance [19,20] to place it within a biological window [21,22]. In addition, strong electric field enhancements due to the presence of multiple sharp tips of AuNSs transform them into high-performance detection materials for surface-enhanced Raman scattering (SERS) [23,24] and surface-enhanced fluorescence (SEF) [25,26]. Properly designed AuNSs can be applied for drug delivery and/or photothermal therapy in the treatment of diseases [16,18] and can be combined with diagnostic mechanisms for surface enhancement in imaging or detection [15,22,26].…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanostars (AuNSs) are of special interest because morphological modifications, such as number of tips and their length, can be used to tune the position of the band of localized surface plasmon resonance [19,20] to place it within a biological window [21,22]. In addition, strong electric field enhancements due to the presence of multiple sharp tips of AuNSs transform them into high-performance detection materials for surface-enhanced Raman scattering (SERS) [23,24] and surface-enhanced fluorescence (SEF) [25,26]. Properly designed AuNSs can be applied for drug delivery and/or photothermal therapy in the treatment of diseases [16,18] and can be combined with diagnostic mechanisms for surface enhancement in imaging or detection [15,22,26].…”
Section: Introductionmentioning
confidence: 99%
“…We attribute these spectral changes to variations in gold nanostar morphology and their resulting plasmonic properties near the excitation wavelength. Because an increase in radius of curvature of the tips of the nanostar branches [11] as well as a decrease in nanostar concentration should cause SERS intensities to decrease, [49] the observed systematic and reproducible increase in SERS magnitude likely depends on branch morphology (i.e., length and aspect ratio) and as a result improved plasmonic properties for SERS enhancement. Namely, as branch aspect ratio (and length) increases, electromagnetic enhancement associated with the bonding (i.e., bright) plasmonic mode becomes more favorable, and plasmonic contributions arising from branch-branch coupling are promoted, thereby increasing the overall SERS signal observed for uranyl through dark plasmon mode [20,36,50] excitation.…”
Section: Sers Detection Of Uranyl Using Tunable Gold Nanostarsmentioning
confidence: 99%
“…The lightning rod or antenna effect associated with anisotropic nanostructures such as gold nanostars makes these materials ideal for substrates in surface‐enhanced Raman scattering (SERS). Previously, it was shown that cubes, [ 1 ] triangles, [ 2,3 ] rods, [ 4–8 ] tetrapods, [ 9 ] and spiked nanostructures (i.e., nanostars) [ 8,10–12 ] are superior substrates for SERS because of the large electromagnetic fields that arise at the near‐field of structural features with small radii of curvature. Gold nanostars, for instance, were previously shown to exhibit large electromagnetic fields near the sharp tips at the ends of their branches.…”
Section: Introductionmentioning
confidence: 99%
“…We found that Au NSs have a higher SERS enhancement as compared to normal gold nanoparticles. 41 These Au NSs with the modification of proper capping agent can be suspended in aqueous media and behaved as colloidal SERS substrates. 41,42 Recently, there are also reports on the use of encoded Au NSs for various applications such as cell discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…41 These Au NSs with the modification of proper capping agent can be suspended in aqueous media and behaved as colloidal SERS substrates. 41,42 Recently, there are also reports on the use of encoded Au NSs for various applications such as cell discrimination. 15,16 However, some of the preparation methods are rather complicated.…”
Section: Introductionmentioning
confidence: 99%